Пошаговое объяснение:
12/(x²+2x) -3/(x²+2x-2)=1
(12(x²+2x-2)-3(x²+2x)-(x²+2x)(x²+2x-2))/((x²+2x)(x²+2x-2))=0
x(x+2)(x²+2x-2)≠0
x≠0
x+2≠0; x≠-2
x²+2x-2≠0
Допустим x²+2x-2=0; D=4+8=12
x₁=(-2-2√3)/2=-1-√3 ⇒ x≠-1-√3
x₂=(-2+2√3)/2=√3 -1 ⇒ x≠√3 -1
12x²+24x-24-3x²-6x-x⁴-2x³+2x²-2x³-4x²+4x=0
7x²+22x-24-x⁴-4x³=0 |×(-1)
x⁴+4x³-7x²-22x+24=0
1 4 -7 -22 24
1 1 5 -2 -24 0
(x-1)(x³+5x²-2x-24)=0
1 5 -2 -24
1 1 6 4 -20
-1 1 4 -6 -18
2 1 7 12 0
(x-1)(x-2)(x²+7x+12)=0
(x-1)(x-2)(x²+3x+4x+12)=0
(x-1)(x-2)(x(x+3)+4(x+3))=0
(x-1)(x-2)(x+3)(x+4)=0
x-1=0; x₁=1
x-2=0; x₂=2
x+3=0; x₃=-3
x+4=0; x₄=-4
ответ: -4; -3; 1; 2.
96-77=19 руб. останется после покупки